Battery charge equalization controller in electric vehicle applications: A review. (August 2017) - Hoque, M.M.; Hannan, M.A.; Mohamed, A.; Ayob, A.
Abstract: The development of electric vehicle (EV) technologies, its applications, energy managements and storage systems are the most important sectors to the automotive industries on their environmental and global economic issues. The electrochemical batteries have a great market in EVs for their long-run and short-run energy storage profiles. Thus, to enhance the battery lifecycle and its performance over the charge and discharge periods, the perfect charge equalization of the long string battery pack is compulsory. The development of new charge equalization controller (CEC) and intensifying the features of existing CECs are now great deal in the field of high-tech storage systems towards the advancement of the sustainable EV technologies. This paper presents the EV technologies with their drive train architectures in different configurations and designs. A study on batteries regarding their formation, properties, energy management systems, advantages and disadvantages are also conducted in the review. A comprehensive review of the different type of CECs for EV applications is highlighted. From the rigorous review, it is concluded that a good equalization controller should have high equalization speed, high efficiency, small volume, simple wiring and execution, low cost and good extensibility. It is observed that the existing CECs have a good contribution to run the EV systems safely and efficiently with their balancing capabilities. However, they still have some problems to achieve all properties for efficient equalization towards the enhancement of battery performance and life. Consequently, a comparison on the salient feature characteristics among the CECs are explained on their topologies, types and execution times, difficulties in control, efficiencies, cost, components, merits and demerits to develop sustainable battery energy storage systems. All the highlighted insights of this review will hopefully lead to increasing efforts towards the development of the advanced CEC for the future high-tech battery energy storage systems in the vehicle applications.